2020
DOI: 10.1186/s40478-020-00936-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and electrophysiological evidence for a neuroprotective role of aquaporin-4 in the 5xFAD transgenic mice model

Abstract: Aquaporin-4 (AQP4) has been suggested to be involved in the pathogenesis of neurodegenerative diseases including Alzheimer's disease (AD), which may be due to the modulation of neuroinflammation or the impairment of interstitial fluid bulk flow system in the central nervous system. Here, we show an age-dependent impairment of several behavioral outcomes in 5xFAD AQP4 null mice. Twenty-four-hour video recordings and computational analyses of their movement revealed that the nighttime motion of AQP4-deficient 5x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 57 publications
(84 reference statements)
1
22
1
Order By: Relevance
“…For a more translational biomarker of potential synaptic abnormalities that lead to cognitive deficits, we evaluated the EEG, which has also been used as a functional biomarker of mild cognitive impairment in patients with AD. Although an abnormal EEG was previously reported in 5XFAD mice on the hybrid background (Schneider et al, 2014;Siwek et al, 2015;Abe et al, 2020), we did not observe significant EEG abnormalities either as indicators of seizure activity, altered synaptic activity related to MCI, or sleep disturbance in this study. Therefore, we do not recommend the 5XFAD model for studies focused on sleep or seizure disturbances in AD or for translational studies evaluating the potential to improve cognitive deficits.…”
Section: Discussioncontrasting
confidence: 80%
“…For a more translational biomarker of potential synaptic abnormalities that lead to cognitive deficits, we evaluated the EEG, which has also been used as a functional biomarker of mild cognitive impairment in patients with AD. Although an abnormal EEG was previously reported in 5XFAD mice on the hybrid background (Schneider et al, 2014;Siwek et al, 2015;Abe et al, 2020), we did not observe significant EEG abnormalities either as indicators of seizure activity, altered synaptic activity related to MCI, or sleep disturbance in this study. Therefore, we do not recommend the 5XFAD model for studies focused on sleep or seizure disturbances in AD or for translational studies evaluating the potential to improve cognitive deficits.…”
Section: Discussioncontrasting
confidence: 80%
“…Indeed, studies performed in AD and CAA transgenic mouse models have confirmed that AQP4 deletion promotes cognitive deficits and increases Aβ accumulation and synaptic damage, suggesting a possible contribution of AQP4 to Aβ clearance through the brain vasculature [ 48 ]. In contrast to these results, in a recent study conducted in 5xFAD mice, an accelerated model of AD with a lower vascular damage contribution, AQP4 deficiency did not induce alterations in Aβ accumulation or in memory deficit [ 49 ]. Nevertheless, experimental evidence suggests that AQP4 may be involved in the clearance of Aβ through perivascular drainage, thus playing a potential protective role in CAA pathology.…”
Section: Discussionmentioning
confidence: 75%
“…As for other FAD mice, to our knowledge there are no reports of tonic-clonic seizures in 5xFAD mice. However, when defined by electroencephalography recordings there are seizures in 5xFAD mice, possibly as early as 4 months ( Abe et al, 2020 ), but that become prevalent at older ages (>10 months) ( Paesler et al, 2015 ; Abe et al, 2020 ; Angel et al, 2020 ). In addition, one proposal is that the abnormal epileptiform activity predisposes 5xFAD mice to convulsive seizures with further stress, as has been demonstrated with genetic approaches ( Paesler et al, 2015 ; Angel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%